Pemanfaatan YouTube sebagai Media Pembelajaran Sosiologi yang Merangsang Minat Belajar Siswa Kelas XI di SMA Negeri 1 Bahorok, Kabupaten Langkat - Br. Peranginangin, Siti Maulida Yani; Mashuri, Kahar; Siregar, Zulham (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2024)
This research aims to investigate the effectiveness of YouTube as a tool to stimulate students' interest in learning sociology. Employing a qualitative research design, data collection methods include observation, interviews, questionnaires, and documentation. Probability sampling, specifically simple random sampling, is utilized to select research participants, including Class XI students from SMA Negeri 1 Bahorok. Researchers administered a questionnaire consisting of 20 statements, both positive and negative, focusing on four indicators of learning interest. The questionnaire aims to gauge students' responses to the use of YouTube in the learning process. Evaluation results reveal a significant increase in student interest, with an average score of 73.0% indicating satisfaction with YouTube-based learning media. Hence, it can be concluded that incorporating YouTube into sociology lessons effectively enhances learning interest among Class XI students at SMA Negeri 1 Bahorok.